MultilingualWikipedia: Editors of Primary Language Contribute to More Complex Articles - Park, Sungjoon; Kim, Suin; Hale, Scott; Kim, Sooyoung; Byun, Jeongmin; Oh, Alice (Proceedings of the International AAAI Conference on Web and Social Media, 2021)
For many people who speak more than one language,their language proficiency for each of the languagesvaries. We can conjecture that people who use onelanguage (primary language) more than another wouldshow higher language proficiency in that primary language.It is, however, difficult to observe and quantifythat problem because natural language use is difficultto collect in large amounts. We identify Wikipedia asa great resource for studying multilingualism, and weconduct a quantitative analysis of the language complexityof primary and non-primary users of English,German, and Spanish. Our preliminary results indicatethat there are indeed consistent differences of languagecomplexity in the Wikipedia articles chosen by primaryand non-primary users, as well as differences in the editsby the two groups of users.